Consumer market segments for biofortified iron beans in Rwanda: Evidence from a hedonic testing study. (January 2017) - Murekezi, Abdoul; Oparinde, Adewale; Birol, Ekin
Highlights: Providing information about the benefits of a new variety is key for its acceptance. Market oriented farmers may not adopt a new technology due to market failures. Poor consumers are less likely to belong to segments associated with expensive beans. The private sector could generate sustained adoption and consumption of iron beans. Abstract: An understanding of consumer market segments is important for efficient and effective targeting of new technologies, such as biofortified foods. In this paper, we use cluster analysis to identify distinct consumer segments in Rwanda for four biofortified iron bean varieties. Data on consumer liking of various sensory attributes of beans was collected by using a 7-point hedonic scale through the application of home-use and central location tests implemented in two rural and two urban locations. Cluster analysis reveals the existence of several distinct consumer segments in each one of the four study locations. Further analysis is conducted by using multinomial probit and logit models to predict consumer segment membership based on the consumer characteristics. Results reveal that, depending on the location, consumer's source of income and whether or not they received information about nutritional benefits of the iron bean varieties have a bearing on their preference of these varieties. The paper presents a profile of each one of the consumer market segments identified to assist targeting of various iron bean delivery, marketing and promotion efforts in Rwanda.